2014
DOI: 10.1017/s0029665113003832
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction and the pursuit of effective mimetics

Abstract: Dietary restriction (DR) has been shown to extend both median and maximum lifespan in a range of animals, although recent findings suggest that these effects are not universally enjoyed across all animals. In particular, the lifespan effect following DR in mice is highly strain-specific and there is little current evidence that DR induces a positive effect on all-cause mortality in non-human primates. However, the positive effects of DR on health appear to be highly conserved across the vast majority of specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 152 publications
1
43
0
2
Order By: Relevance
“…Exactly how they generate the health benefits remains open for debate, however CR results in promoted oxidative stress resistance, enhanced autophagy, and a generalized shift from carbohydrate to fat metabolism, all of which could be essential components of the beneficial effects (Selman, 2014;Speakman and Mitchell, 2011). As described previously, our experiments showed that worms treated with rBTI showed increased oxidative stress resistance.…”
Section: Rbti Decreases Glycolysis Increased Lipolysis and Induced supporting
confidence: 75%
See 2 more Smart Citations
“…Exactly how they generate the health benefits remains open for debate, however CR results in promoted oxidative stress resistance, enhanced autophagy, and a generalized shift from carbohydrate to fat metabolism, all of which could be essential components of the beneficial effects (Selman, 2014;Speakman and Mitchell, 2011). As described previously, our experiments showed that worms treated with rBTI showed increased oxidative stress resistance.…”
Section: Rbti Decreases Glycolysis Increased Lipolysis and Induced supporting
confidence: 75%
“…We hypothesized that rBTI elicits its beneficial effects by mimicking CR, and CR has been linked to increased AMP:ATP ratio, respiration and transient ROS signal (Masoro, 2005;Selman, 2014). As reported by others (Boveris and Chance, 1973;Kemp et al, 2003), increased AMP could induce respiration, and ROS generation is increased by respiration, as inevitable by-product of respiration.…”
Section: Rbti Increases Amp:atp Ratio and Respiration Induces A Tranmentioning
confidence: 82%
See 1 more Smart Citation
“…DR 25 had no effect on hepatic protein levels of PGC-1a, TFAM, and OXPHOS complexes skeletal muscle mitochondria. We highlight tissue-specific differences in the critical factor that may help explain the unresponsiveness of particular organisms to 68 DR-induced longevity is genetic background [1], [7], [18], [19]. For example, the 69 effect of DR on survival in DBA/2 mice has been a source of debate for many years, 70 with DR reported to extend [20], [21], have no effect [22], or shorten lifespan [14].…”
mentioning
confidence: 99%
“…First identified in rats and mice at the beginning of the last century, restricting food intake in rodents prolonged longevity (McDonald & Ramsey, 2010). Ever since, except for a few exceptions (Selman, 2014;Speakman & Hambly, 2007), food restriction has increased the life span of all organisms tested (Fontana et al, 2010;Mair & Dillin, 2008;Trepanowski, Canale, Marshall, Kabir, & Bloomer, 2011).…”
Section: Dr and The Nutrient-sensing Networkmentioning
confidence: 99%